POTENSI PENERAPAN SELF-HEALING CONCRETE UNTUK MENINGKATKAN KETAHANAN INFRASTRUKTUR DI WILAYAH RAWAN GEMPA: STUDI KASUS SUMATERA BARAT - Badzlina Harvy Nesya; Rahmad Suryadi; Shafwan; Ahsanul Ihsan; Salsa Fadilah; Radit Virdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia, located in one of the world’s most active seismic zones, faces major challenges in maintaining infrastructure resilience against earthquakes. Structural damage caused by microcracks in conventional concrete often leads to performance degradation and high maintenance costs. This study examines the potential application of Self-Healing Concrete (SHC) as an innovative material to enhance infrastructure durability in earthquake-prone regions, particularly in West Sumatra. SHC functions through biological and chemical mechanisms, where agents such as Bacillus subtilis and calcium lactate produce calcium carbonate (CaCO₃) to autonomously seal cracks. Findings indicate that SHC can increase concrete durability by up to 20%, reduce water permeability by 45%, and extend the service life of structures by more than two decades. Moreover, SHC supports carbon emission reduction and promotes sustainable resilient infrastructure. Therefore, the implementation of SHC represents a strategic approach to achieving durable, efficient, and environmentally friendly infrastructure in Indonesia’s seismic regions.